Peran Konten Buatan Pengguna dalam Membentuk Kepercayaan Konsumen: Pendekatan Psikologi Komunikasi terhadap E-commerce - Alamyar, Iqbal Hussain; Kurniawati, Henie (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2024)
User-Generated Content (UGC) plays a vital role in shaping consumer trust within the dynamic realm of e-commerce. This study explores the psychological mechanisms through which UGC influences trust, employing a communication psychology approach. Using qualitative interviews with frequent e-commerce users, the research investigates how UGC impacts trust and the psychological factors involved. Thematic analysis of participant responses revealed key themes, including perceived authenticity, community engagement, and content creator relatability. Participants emphasized that genuine and relatable UGC enhances transparency and trustworthiness, setting it apart from traditional advertising. Additionally, social proof and cognitive biases were found to significantly influence trust formation. Findings suggest that e-commerce platforms can enhance consumer trust by fostering authentic UGC and encouraging active community engagement. This research provides valuable insights into the interaction between digital content and consumer behavior, offering practical strategies for leveraging UGC, such as promoting genuine user participation and integrating UGC into marketing efforts. This study highlights the critical role of UGC in building trust in e-commerce, contributing to the theoretical framework of communication psychology while bridging the gap between theory and practice.